Assessment of atmospheric heavy metal deposition using moss Plagiomnium undulatum by active biomonitoring in Almora city, Uttarakhand (India) - Priyank Chaturvedi; Shiv Om Singh; Kajal S. Rathore (Environment Conservation Journal)
Mosses, particularly Plagiomnium undulatum, are effective bioindicators for monitoring environmental contamination, especially from heavy metals of both natural and anthropogenic origins. This research explored spatial and temporal variations in atmospheric metal deposition in Almora city, Uttarakhand, using active biomonitoring techniques. Moss samples were collected from Mukteshwar due to the limited anthropogenic activity, relatively clean air, and absence of major industrial activity, making it suitable for baseline comparison. In contrast, within Almora, samples were transplanted at 0.5 km, 1.0 km, and 3.0 km distances in all cardinal directions to monitor the spatial variation in heavy metal deposition. The concentrations of nine heavy metals (Al, Mn, Fe, Ni, Cu, Zn, As, Cd, and Pb) were analyzed using Inductively Coupled Plasma Mass Spectrometry (ICP-MS). Metal deposition followed the   seasonal order: summer > winter > monsoon. During the summer, the highest      concentrations of metals in Plagiomnium undulatum were recorded at a distance of 0.5 km from the center of Almora city. The highest recorded concentrations were Fe (27,038.27 μg/g, East), Al (26,263.84 μg/g, South), Mn (304.04 μg/g, South), and Zn (179.27 μg/g, East). Additionally, metals like Cu, Ni, As, Cd, and Pb showed elevated levels in summer and winter compared to the monsoon season. However, the pronounced seasonal variation could primarily be caused by peak gasoline consumption during the summer, followed by winter due to a significant increase in tourist activities. The metal concentration order across all seasons was Fe > Al > Mn > Zn > Ni > Cu > As > Pb > Cd. These findings confirm that P. undulatum is a reliable marker of the spatial and seasonal variability of atmospheric metal concentration. Heavy metals in the air principally come from industrial emissions during metal fabrication, vehicular activities, forest fires, and natural processes such as soil erosion, dust, and snowmelt. In addition, the research illustrates the role of topography and hilly terrain on air quality with the potential implication for human health, agricultural output, and ecosystem equilibrium and its importance for sustaining air pollution management.